Spectroscopic Characterization of a Reactive [Cu2 (μ-OH)2 ]2+ Intermediate in Cu/TEMPO Catalyzed Aerobic Alcohol Oxidation Reaction - Warm, Katrin; Tripodi, Guilherme; Andris, Erik; Mebs, Stefan; Kuhlmann, Uwe; Dau, Holger; Hildebrandt, Peter; Roithová, Jana; Ray, Kallol (Angewandte Chemie (International ed. in English), 2021)
CuI /TEMPO (TEMPO=2,2,6,6-tetramethylpiperidinyloxyl) catalyst systems are versatile catalysts for aerobic alcohol oxidation reactions to selectively yield aldehydes. However, several aspects of the mechanism are yet unresolved, mainly because of the lack of identification of any reactive intermediates. Herein, we report the synthesis and characterization of a dinuclear [L12 Cu2 ]2+ complex 1, which in presence of TEMPO can couple the catalytic 4 H+ /4 e- reduction of O2 to water to the oxidation of benzylic and aliphatic alcohols. The mechanisms of the O2 -reduction and alcohol oxidation reactions have been clarified by the spectroscopic detection of the reactive intermediates in the gas and condensed phases, as well as by kinetic studies on each step in the catalytic cycles. Bis(μ-oxo)dicopper(III) (2) and bis(μ-hydroxo)dicopper(II) species 3 are shown as viable reactants in oxidation catalysis. The present study provides deep mechanistic insight into the aerobic oxidation of alcohols that should serve as a valuable foundation for ongoing efforts dedicated towards the understanding of transition-metal catalysts involving redox-active organic cocatalysts.
Keywords: reactive intermediates; stopped-flow kinetics; copper; dioxygen reduction; alcohol oxidation